Direct Brow Lift and Skin Contraction in Facial Nerve Palsy: A Switch Technique. (May 2021) - Nagendran, Sonali T.; Butler, Daniel; Malhotra, Raman
Abstract : The authors present a case series of 4 patients with facial nerve palsy who underwent a direct brow lift to correct brow ptosis, using the excised brow skin as a full-thickness skin graft to correct lower eyelid skin contracture, ectropion, and retraction. Functional outcomes were measured using the validated cornea, static asymmetry, dynamic function, synkinesis (CADS) grading system and by photographic assessment of lower eyelid height via margin reflex distance. Aesthetic outcomes were measured using a published grading scale specific to eyelid skin grafts. Abstract : The authors present outcomes and remind readers of the usefulness of excised direct brow lift skin for lower eyelid ectropion and retraction where skin contracture exists in facial nerve palsy.